2018
DOI: 10.1039/c8en00436f
|View full text |Cite
|
Sign up to set email alerts
|

Metal oxide nanoparticles alter peanut (Arachis hypogaea L.) physiological response and reduce nutritional quality: a life cycle study

Abstract: We investigate the effects of metal oxide NPs, Fe2O3, CuO, and TiO2, on peanuts (Arachis hypogaea L.) in a full life cycle study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 83 publications
0
42
0
1
Order By: Relevance
“…Other published studies are the oxide NPs such as the ones evaluated by Rui et al [ 101 , 102 ] concerning full life cycle of the impacts of metal NPs including iron oxide (Fe 2 O 3 ) and copper oxide (CuO) at 50 and 500 mg/kg. Results showed that all the nanomaterials caused a decrease in the concentration of total amino acids, except for 50 mg/kg TiO 2 NPs, when peanut grains ( Arachis hypogaea ) were examined.…”
Section: Environmental Negative Impactmentioning
confidence: 99%
“…Other published studies are the oxide NPs such as the ones evaluated by Rui et al [ 101 , 102 ] concerning full life cycle of the impacts of metal NPs including iron oxide (Fe 2 O 3 ) and copper oxide (CuO) at 50 and 500 mg/kg. Results showed that all the nanomaterials caused a decrease in the concentration of total amino acids, except for 50 mg/kg TiO 2 NPs, when peanut grains ( Arachis hypogaea ) were examined.…”
Section: Environmental Negative Impactmentioning
confidence: 99%
“…The seed presowing with ZnO NPs may change the nutrient contents in seeds affecting plant growth, yield and quality (Rui et al, 2018;Rizwan et al, 2019). For instance, the application of ZnO NPs (22.4 nm, 10 mg L À1 ) increase the shoot and root length of Vigna radiate concomitant with activation of phosphorus mobilizing enzymes and phosphorus uptake by 10.8% (Raliya et al, 2016).…”
Section: Seedlings Growth Characters As Affected By the Metal Oxide Nmentioning
confidence: 99%
“…However, most of these methods involved the direct addition of the NP fertilizer to the soil or the hydroponic system, which is less attractive in terms of environmental sustainability. Studies have shown stress response and reduction of amino acids in plants with excess addition of NP fertilizers [20]. There is a need for a new environmental-friendly strategy that increases plant growth with a minimum quantity of the fertilizer while also minimizing the addition of fertilizer to the environment.…”
Section: Introductionmentioning
confidence: 99%